Validity of computed tomography defined body composition as a prognostic factor for functional outcome after kidney transplantation - Tim D. A. Swaab; Evelien E. Quint; Lisa B. Westenberg; Marcel Zorgdrager; Dorry L. Segev; Mara A. McAdams‐DeMarco; Stephan J. L. Bakker; Alain R. Viddeleer; Robert A. Pol (Wiley, 2023)
Abstract Background The prevalence of sarcopenia is markedly higher in kidney transplant candidates than in the general population. It is a syndrome characterized by progressive and generalized loss of skeletal muscle mass and strength, which increases the risk of adverse postoperative outcomes. Methods We studied the impact of computed tomography defined preoperative sarcopenia, defined as a skeletal muscle index below age and gender specific cut‐off values, on postoperative physical functional outcomes (grip strength, 4‐m walking test, timed up and go, and sit to stand) at 6 months follow up. Results A total of 107 patients transplanted between 2015 and 2019 were included in this single‐centre study. Mean age was 60.3 (±13.1), and 68.2% of patients were male. Ten patients (9.4%) were identified as sarcopenic. Sarcopenic patients were younger (55.6 (±15.1) vs. 60.8 (±12.9) years), more likely to be female (60.0% vs. 28.9%), and had an increased dialysis vintage (19 [2.5-32.8] vs. 9 [0.0-21.0] months) in comparison with their non‐sarcopenic counterparts. In univariate analysis, they had a significantly lower body mass index and skeletal muscle area (P ≤ 0.001). In multivariate regression analysis, skeletal muscle index was significantly associated with grip strength (β = 0.690, R2 = 0.232) and timed up and go performance (β = −0.070, R2 = 0.154). Conclusions We identified a significant association between sarcopenia existing pre‐transplantation and poorer 6 months post‐transplantation physical functioning with respect to hand grip strength and timed up and go tests in kidney transplant recipients. These results could be used to preoperatively identify patients with an increased risk of poor postoperative physical functional outcome, allowing for preoperative interventions to mitigate these risks.